You are on page 1of 4


Find your Friend
Directions: I will hand you a function. Walk around the room and pair up with someone. You choose a
number and plug that number into their function. Then they will give you their result and you plug that result
into your function. Do you notice anything? Now do it again but have them choose the first number. When
you find someone whose function, when composed with yours gives you an interesting result, pair up and
complete the worksheet below.
Your function:__________________ Your friends function:____________________
Fill out the chart. Use youโ€™re functions outputs as the inputs for your friendโ€™s function.

๐‘ฅ Original ๐‘ฅ 0 1 4 9 โˆ’1 16

๐‘ฆ Your

๐‘ฅ Your
๐‘ฆ Your friendโ€™s
What relationship does your function have to your friendโ€™s function? Explain in complete sentences.

Draw maps of what your function does to ๐‘ฅ using the circles below. Hereโ€™s an example of how to do it. The
function map for ๐‘“(๐‘ฅ) = 3๐‘ฅ + 2 would be:
ร—3 +2
๐‘ฅ 3๐‘ฅ 3๐‘ฅ + 2

Your function

Your partnerโ€™s function

What do you notice?
Based on the charts above, can you write the inverse of the function ๐‘”(๐‘ฅ) = 2๐‘ฅ + 10?

If your function takes in 3 and outputs 5, what would one input, output pair be for your partnerโ€™s function?

Do that again for each of the following
Your function intakes โˆ’2 Your function intakes Your function intakes ๐‘Ž Your function intakes ๐‘ฅ
and outputs 9 โˆ’5.4 and outputs โˆ’92 and outputs ๐‘ and outputs ๐‘ฆ
Your partnerโ€™s function Your partnerโ€™s function Your partnerโ€™s function Your partnerโ€™s function
would: would: would: would:

Now rename your function as ๐‘“(๐‘ฅ) and rename your partnerโ€™s function as ๐‘”(๐‘ฅ). Compute each of the

a. ๐‘“(๐‘”(1)) b. ๐‘”(๐‘“(5)) c. ๐‘“(๐‘”(4583))

d. ๐‘”(๐‘“(4.04727462)) e. ๐‘“(๐‘”(๐‘Ž)) f. ๐‘”(๐‘“(๐‘))

Graph both functions carefully on the grid below. Use the
table above or tables on your calculator to be very precise.
What do you notice?

( )
๐‘— ๐‘ฅ = ๐‘ฅ+1 ๐‘”(๐‘ฅ ) = 3๐‘ฅ โˆ’ 9

๐‘–(๐‘ฅ ) = โˆš๐‘ฅ ๐‘”(๐‘ฅ ) =

1 ๐‘Ÿ(๐‘ฅ ) = 2๐‘ฅ + 4
( )
๐‘” ๐‘ฅ = ๐‘ฅ+3

๐‘˜(๐‘ฅ ) = ๐‘ฅ 2 ๐‘˜(๐‘ฅ ) = ๐‘ฅ + 3

๐‘›(๐‘ฅ ) = ๐‘ฅ โˆ’ 7 ๐‘ž(๐‘ฅ ) = ๐‘ฅ + 7

๐‘(๐‘ฅ ) = โˆš๐‘ฅ + 1 ๐‘“ (๐‘ฅ ) = 3๐‘ฅ + 3

โ„Ž(๐‘ฅ ) = ๐‘ฅ 2 โˆ’ 1 ๐‘š(๐‘ฅ ) = 2๐‘ฅ โˆ’ 6

๐‘“(๐‘ฅ ) = 4๐‘ฅ ๐‘™ (๐‘ฅ ) = ๐‘ฅ